2016
DOI: 10.1111/ajt.13704
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapy for Parkinson’s Disease: A Translational Approach to Assess the Role of Local and Systemic Immunosuppression

Abstract: Neural transplantation is a promising therapeutic approach for neurodegenerative diseases; however, many patients receiving intracerebral fetal allografts exhibit signs of immunization to donor antigens that could compromise the graft. In this context, we intracerebrally transplanted mesencephalic pig xenografts into primates to identify a suitable strategy to enable long-term cell survival, maturation, and differentiation. Parkinsonian primates received WT or CTLA4-Ig transgenic porcine xenografts and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Martin et al produced transgenic pigs with neuronal expression of hCTLA4-Ig and demonstrated that hCTLA4-Ig protein reduced the proliferation of human T cells against porcine cells (103). The beneficial effect of hCTL4-Ig expression extended xenograft survival time in a rat skin transplantation model (104) and a NHP neuronal transplantation model (137). These in vivo evidence also suggested that the expression of hCTLA4-Ig alone could not prevent xenograft rejection, which is consistent with the result blocking costimulatory pathway against B7-CD28 only.…”
Section: Inhibition Of Cellular Xenograft Rejectionmentioning
confidence: 70%
“…Martin et al produced transgenic pigs with neuronal expression of hCTLA4-Ig and demonstrated that hCTLA4-Ig protein reduced the proliferation of human T cells against porcine cells (103). The beneficial effect of hCTL4-Ig expression extended xenograft survival time in a rat skin transplantation model (104) and a NHP neuronal transplantation model (137). These in vivo evidence also suggested that the expression of hCTLA4-Ig alone could not prevent xenograft rejection, which is consistent with the result blocking costimulatory pathway against B7-CD28 only.…”
Section: Inhibition Of Cellular Xenograft Rejectionmentioning
confidence: 70%
“…1317 Genetically engineered mesencephalic pig cells have reduced the physical features of a Parkinson-like disease in monkeys for more than 1 year. 18 Even in the difficult pig-to-baboon liver transplantation model, there has been significant improvement in graft survival, to almost 1 month in 2 recent instances. 1921 …”
Section: Preclinical Progressmentioning
confidence: 99%
“…One of them include the neuroinflammation that gave rise to their death . Post mortem studies have substantially confirmed the involvement of innate as well as adaptive immunity in the affected brain regions in PD patients . Furthermore, activated microglial cells and T lymphocytes have also been detected in the substantia nigra of patients concomitantly with an increased expression of proinflammatory mediators .…”
Section: Introductionmentioning
confidence: 95%